1961
DOI: 10.1037/h0042260
|View full text |Cite
|
Sign up to set email alerts
|

The current status of the size-distance hypotheses.

Abstract: In the history of the psychology of perception few matters have been of more continuous interest than the relationship between perceived size and perceived distance. It is our objective to examine the current status of this question by reviewing the recent literature. With some exceptions our review will be confined to investigations which have been reported since 1952. Several surveys of the literature prior to 1952 are available, and for this reason we will have relatively little to say about these earlier i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
0
1

Year Published

1966
1966
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(139 citation statements)
references
References 70 publications
10
128
0
1
Order By: Relevance
“…While specific predictions may be affected, the general validity of the current hypothesis does not depend on the outcome of this debate 13 A few subjects reported perceiving smaller but more remote objects, or closer but bigger objects. This pattern of responses is consistent with reporting biases linked to the size-distance paradox, (Epstein et al, 1961;Gogel, 1990 Note: Descriptions are drawn from reports by 20 subjects who reported a better impression of depth in the monocular-aperture condition. Size and distance were treated as a single category because of known dependencies and interactions in reports of these two attributes (the size-distance paradox).…”
Section: Monocular Stereopsis and Changes In Perceived Distance And Sizesupporting
confidence: 70%
See 1 more Smart Citation
“…While specific predictions may be affected, the general validity of the current hypothesis does not depend on the outcome of this debate 13 A few subjects reported perceiving smaller but more remote objects, or closer but bigger objects. This pattern of responses is consistent with reporting biases linked to the size-distance paradox, (Epstein et al, 1961;Gogel, 1990 Note: Descriptions are drawn from reports by 20 subjects who reported a better impression of depth in the monocular-aperture condition. Size and distance were treated as a single category because of known dependencies and interactions in reports of these two attributes (the size-distance paradox).…”
Section: Monocular Stereopsis and Changes In Perceived Distance And Sizesupporting
confidence: 70%
“…Epstein, Park & Casey, 1961;Kaufman & Rock, 1962;McCready, 1965;Gogel, 1990). I will not address this complex debate here as it is outside of the scope of this manuscript.…”
Section: Monocular Stereopsis and Changes In Perceived Distance And Sizementioning
confidence: 99%
“…The apparent size of a familiar object yields much meaningful information regarding its distance from the observer. Hodge (1981) argues that though there are reservations regarding Gogel's perceptual model (Epstein, Park, & Casey, 1961) the role of relative and familiar size cues to relative depth are fairly reasonable cues to space perception. Ono (1970) states that "familiar size can serve as a source of information for scalar tasks because familiar objects yield a specific retinal image size at a given distance, and this, in conjunction with the knowledge of the frontal extent of the object, can be utilized as information for the egocentric extent between the observer and the familiar object."…”
Section: --7_mentioning
confidence: 99%
“…The manner of determining height and the geometry shown in Figure 6 is suggestive of a perceptual hypothesis which has attracted much research attention -the Size-Distance Invariance Hypothesis (Hochberg, 1971;Epstein, Park, & Casey, 1961;Kilpatrick & Ittelson, 1953). This is portrayed in Figure 7.…”
Section: Low Level Flightmentioning
confidence: 99%
“…The suggestion of Epstein et al (1961) is that the perceptions of height and distance are individually determined. They comment that, though height and distance are physically related and though an impression of either or both can usually be obtained in most situations, their perceived magnitudes are not necessarily related.…”
Section: Low Level Flightmentioning
confidence: 99%